THE LEGAL INSTITUTION OF THE POWER OF ATTORNEY IN POLISH AND ITALIAN LEGAL SYSTEMS. ANALYSIS OF TERMINOLOGY AND TRANSLATION STRATEGIES - BIERNACKA-LICZNAR, Katarzyna (Comparative Legilinguistics, 2014)
The aim of the article is to study the basic terminology and phraseology referring to the institution of the power of attorney. The article gives outline information about the legal institution of power of attorney in Polish and Italian legal systems, as well as definitions of some related concepts, which can constitute a basis for a methodological frame of reference and a repertory of practical guidelines and suggestions regarding the process of translation. Due to the changeability of the term in question and its polysemous character, an attempt has been made to show the basic terminology present in both languages: Polish and Italian and their equivalents. Detailed information concerning the power of attorney in the form of notary deed in the Italian legal order have been compared with the requirements as to construction of the notary deedenvisaged in the Polish act on notaryship. The article presents the results of the analysis carried out on ten selected documents of the power of attorney in Italian, which led to the making of a Polish-Italian glossary of the terminology in question. Presentation and explanation of the importance of linguistic and dogmatic meaning of selected Italian phrases and rules referring to the documents of the power of attorney has been accompanied by reflection on translator training practice.